Orthohantaviruses: An Overview of the Current Status of Diagnostics and Surveillance - Maria Anele Romeo; Silvia Tofani; Daniele Lapa; Cosmina Mija; Fabrizio Maggi; Maria Teresa Scicluna; Roberto Nardini (Viruses)
Orthohantavirus infection is a rodent-to-human zoonotic disease with a worldwide distribution, resulting in more than 200,000 cases per year. Human infection leads to two diseases, haemorrhagic fever with renal syndrome and hantavirus cardiopulmonary syndrome, with mortality rates ranging from 1% to 38%. Apart from the data on cases presenting obvious clinical symptoms, the true prevalence is poorly understood, especially in the occupational groups considered to be at risk of exposure. As there is currently no approved therapy or vaccine, surveillance is essential to locate the presumed site of infection following orthohantavirus outbreaks in order to control the spread of infection. To this end, the use of rapid diagnostic tools is essential to rapidly provide data on viral circulation. This review focuses mainly on the available diagnostic methods, both serological and biomolecular, and the surveillance systems used for orthohantaviruses. The information gathered could provide a valid basis for the implementation of further surveillance systems in a country lacking up-to-date data.